The Influence of Price and Product Quality on Customer Engagement Based on Perceived Value with a Budgeting Perspective in a Family-Owned Livestock Business - Ni Putu Lisa Wijayanti; Gde Deny Larasdiputra; I Putu Gde Chandra Artha Aryasa (Journal of Governance, Taxation and Auditing, 2026)
This study aims to examine the influence of price and product quality on Customer Engagement based on perceived value from a budgeting perspective in a family-owned livestock business. The research employed a quantitative approach using primary data collected through questionnaires distributed to 75 consumers of Lisa Pig Farm. Data were analyzed using multiple linear regression with SPSS software. The results indicate that price has a significant effect on Customer Engagement, product quality has a significant effect on Customer Engagement, and both price and product quality simultaneously have a significant effect on Customer Engagement, with a coefficient of determination (R²) of 0.654. These findings suggest that budgeting decisions reflected in pricing strategies and quality management contribute to the formation of positive perceived value and enhance customer engagement. This study extends the role of Customer Engagement as a non-financial indicator in management accounting and entrepreneurial accounting to evaluate market-based business sustainability.